PENINGKATAN MUTU DAN EFISIENSI PELAYANAN KESEHATAN MELALUI IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT HASTA HUSADA: Improving the Quality and Efficiency of Health Services through the Implementation of Electronic Medical Records (RME) at Hasta Husada Hospital - Rusdi, Achmad Jaelani; Kurniawan, Fendi; Rifqi, Amir Muhammad (Forind Press, 2024)
Implementation of electronic medical records (RME) in hospitals has become an important step in improving the quality and efficiency of health services. Hasta Husada Hospital has adopted this system, but still faces various challenges. This study aims to analyze and evaluate improving the quality and efficiency of health services through the implementation of electronic medical records (RME) at Hasta Husada Hospital. This research uses a qualitative approach. The research results show that RME provides significant benefits, including fast and accurate access to patient data, increased work efficiency, and reduced medical errors. Although most users feel comfortable using RME after training, there are still complaints about the system interface needing to be simplified. User attitudes were generally positive towards RME after seeing real benefits, despite initial resistance. Implementation of the Hospital Management Information System (SIMRS) has shown mixed results, with some units having fully transitioned to RME and others still in the transition stage.